2016
DOI: 10.1111/eos.12297
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation may explain why females are less susceptible to dental erosion

Abstract: Not all individuals at risk for dental erosion (DE) display erosive lesions. The prevalence of DE is higher among male subjects. The occurrence of DE may depend on more than just acidic challenge, with genetics possibly playing a role. The aim of this study was to investigate the association of enamel-formation genes with DE. One premolar and a saliva sample were collected from 90 individuals. Prepared teeth were immersed in 0.01 M HCl (pH 2.2), and enamel loss (μm) was measured using white light interferometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
1
16
0
4
Order By: Relevance
“…Regarding statistical analysis, similarly to the family-based study also using the TDT reported by Vieira et al [2004], we decided not to apply the Bonferroni correction to our results since it would reduce the α-value to 0.004 (0.05/11 SNPs). This would increase the type II error [Uhlen et al, 2016;Vieira et al, 2017], which would lead us to reject a hypothesis of a true biological association. The use of these corrections may prevent the identification of discrete biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding statistical analysis, similarly to the family-based study also using the TDT reported by Vieira et al [2004], we decided not to apply the Bonferroni correction to our results since it would reduce the α-value to 0.004 (0.05/11 SNPs). This would increase the type II error [Uhlen et al, 2016;Vieira et al, 2017], which would lead us to reject a hypothesis of a true biological association. The use of these corrections may prevent the identification of discrete biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a genetic association between dental caries and polymorphisms in genes associated with the mineralization of bone, formation of enamel, microbial colonization and the degradation of amelogenin, which is an essential step in enamel formation [1][2][3][4][5]. Other studies have shown that the formation of dental enamel is influenced by genetic variation and can impact the prevalence of dental caries [6]. Further, it has also been shown that mouse dental enamel with less amelogenin is "weaker" than enamel with normal levels of amelogenin [7].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the influences of these potentially confounding factors on our results, only one surface of one type of tooth was used in the present study (the buccal surface of sound premolars that were extracted for orthodontic reasons), and 150–200 μm of the surface enamel was removed in a controlled manner using a Vernier caliper. Previous studies of the correlations between changes in acid-induced enamel microhardness or demineralization-associated lesions and genetic variations in enamel formation genes included small samples of 28 and 90 subjects (Shimizu et al, 2012 ; Uhlen et al, 2016 ). The present study included 213 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic association studies of dental caries have suggested that caries may be influenced by variations in enamel formation genes, such as ameloblastin ( AMBN ), amelogenin ( AMELX ), enamelin ( ENAM ), matrix metalloproteinase 20 ( MMP20 ), tuftelin ( TUFT1 ), and tuftelin-interacting protein 11 ( TFIP11 ) (Shimizu et al, 2012 ; Wang et al, 2012 ; Gasse et al, 2013 ; Shaffer et al, 2015 ; Gerreth et al, 2016 ). Previous studies have sought to explain how enamel formation genes influence caries susceptibility (Shimizu et al, 2012 ; Daubert et al, 2016 ; Uhlen et al, 2016 ). One hypothesis is that variation in these genes results in the formation of enamel that is more susceptible to cariogenic challenge (Shimizu et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%